(untitled) (Fiep Bulletin - online, 2013)
This study aimed to verify and analyze the child’s satisfaction with their distribution of body fat (score of discrepancies) and the influence it exerts on your body image as one of the images contained on a scale of 9 profiles corporais proposed by Stunkard and Sorensen ( 1993). This study is a descriptive qualitative, because you are dealing with body image and quantitative (THOMAS AND NELSON, 2002). The subjects of the study volunteers will be 50 people with visual disabilities, all female volunteers with 25 patients with congenital visual disability and 25 individuals with visual impairments acquired. The study will collect data on their Benjamin Constant Institute located in the city Rio de Janeiro, all female, aged between 14 and 30 years and who wish to participate in the study. The results show that there was a significant difference between the blind and visually impaired acquired congenital, since both had a good body awareness, and the concept of beauty given by them is the same as the company now feels as standard. This shows us that both those acquired in the congenital, despite all the difference in a day Tuesday sight, have a goal or a desire to have a body that fits in the standard of beauty imposed by society.